CHANGES IN THE INTEREPITHELIAL LYMPHOCYTES OF THE MUCOUS MEMBRANE OF THE SMALL INTESTINE WHEN EXPOSED TO HERBICIDES - Tukhsanova Nasiba Esanovna (Scholar Express Journals, 2023)
The article analyzes the quantitative composition of lymphocytes of the epithelial cover of the mucous membrane of the small intestine in normal and under the influence of the herbicide kotorana. In the experiment, when exposed to cotoran, an increase in the number of large and medium lymphocytes is noticeable, and by the age of 3 months, the number of large, medium and small lymphocytes approaches the indicators of the control group.
Keywords: Peyer's plaques; cotoran; lymphocytes; germinative center